-(7x+1)-(-5x+9)=

Simple and best practice solution for -(7x+1)-(-5x+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7x+1)-(-5x+9)= equation:


Simplifying
-1(7x + 1) + -1(-5x + 9) = 0

Reorder the terms:
-1(1 + 7x) + -1(-5x + 9) = 0
(1 * -1 + 7x * -1) + -1(-5x + 9) = 0
(-1 + -7x) + -1(-5x + 9) = 0

Reorder the terms:
-1 + -7x + -1(9 + -5x) = 0
-1 + -7x + (9 * -1 + -5x * -1) = 0
-1 + -7x + (-9 + 5x) = 0

Reorder the terms:
-1 + -9 + -7x + 5x = 0

Combine like terms: -1 + -9 = -10
-10 + -7x + 5x = 0

Combine like terms: -7x + 5x = -2x
-10 + -2x = 0

Solving
-10 + -2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -2x = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -2x = 0 + 10
-2x = 0 + 10

Combine like terms: 0 + 10 = 10
-2x = 10

Divide each side by '-2'.
x = -5

Simplifying
x = -5

See similar equations:

| 1/6(12z-18=2z-3 | | 18*2/3-4 | | 3x(x^2-2)= | | 2/3*18-4 | | 27+4.5x= | | 5+2(x-3)=2[5-4x(x+2)] | | 9x-1(3x-1)=2 | | 5(3x+2)=8x-14-x | | 3/x(2)-5=7 | | 2x=-60 | | 32x-17x+55=100 | | logx-564=2 | | ((a^2)-(x^2))^(1/2) | | 4x(x-5)=3x+7 | | 83+-3x=55 | | 0.625*x^2-1.5*x-5=0 | | -8n-8=-72 | | f(-3)=2+2 | | 29x+7y=-17 | | 8h-5=11-14 | | 36a^2-49b^2= | | 0.9/7.2 | | 96/-5 | | -18-21x=8x-106 | | 15+0.75x=9+1.50x | | 3-1x=17 | | 5x^4(x^2)=0 | | 0.9x-6=0.3x+30 | | 85,88-86,242/(-0,0715) | | F(x)=45-3x | | 3(a+6)=10[a-(5-a)] | | 7x-5y=-140 |

Equations solver categories